CHILDREN, CHILDHOODS AND EDUCATION IN THE PAGES OF THE NEWSPAPER ESTADO DE MINAS IN THE 1930Swspaper Estado de Minas in the 1930s - Sousa Soares, Ademilson de (Historia y Memoria de la Educación, 2024)
The article presents and analyzes conceptions of children, childhood and education contained in the pages of the Estado de Minas newspaper in the 1930s, indicating the existence of two predominant tendencies within the news: one new, more liberal and modern, called Americanism; the other old, more conservative and traditional, called Iberian Federalism. The interpretation of the news’ contents occurred based on authors such as Bardin (1988), Werneck Vianna (1997), Nunes (1998) and Guimarães (2013), among others, aiming to systemize, group, describe and categorize the conveyed messages. As a result, it is shown that the symbiosis between the Brazil that intends to emerge and the Brazil that insists on remaining stems from the moral, medical and psychological discourses which leave their mark on the debate about the assistance and education of the children. The newspaper Estado de Minas, as a space of ideological dispute for the power to form the Brazilian people and nation was not immune to this movement and this simbisosis. Liberals americanists advocate schoolnovism. Conservatives iberics defended religious and Christian education with fervor. However, the crisis of capitalism in the world manifested in the American crisis of the 1930s does not cease to appear in the pages of the newspaper and the educational debate.